Modelos de otimização para avaliação de investimentos em redes de distribuição de energia elétrica considerando índices de confiabilidade - Caetano, Ana Paula Pereira Tsuyuguchi (2015)
The simulation results obtained using three models which minimize the distribution system reliability indexes and investment through sectionalizing switches allocation and/ or installation of tie lines are presented in this work. This is a problem with conflicting goals that were simultaneously minimized through a multi-objective Genetic Algorithm (Non- Dominated Sorting Genetic Algorithm II - NSGA II), seeking trade-off solutions between investment costs and network reliability. As constraints, the continuity indexes (DEC and FEC) and the power flow of the system were considered. The three models presented have two objective functions, being the first one the investment cost (CINV) of allocated equipment. The second function is one of three reliability indexes: Cost of Energy not Supplied (CENS), DEC and FEC. In the first model (CINV and CENS), results with higher quantities of sectionalizing switches allocation were found, so it was the model which presented higher investment costs. In the second model (CINV and DEC) results presenting lower values for the DEC were found, comparing with the first model, and lower investment cost, but the total cost were similar to those of the first model, since it has an increased CENS. The third model (CINV and FEC) was the model which allocated less sectionalizing switches and presented lower investment costs, since the allocation of these devices do not influence the minimization of FEC, only the allocation of tie lines change the system configuration influencing the FEC. All results obtained through the models met the expectations of finding a set of diverse solution considering the constraints.